Recent advances in the treatment of type 2 diabetes mellitus using new drug therapies - Keong Chong; Jack Keng‐Jui Chang; Lee‐Ming Chuang (Kaohsiung Journal of Medical Sciences, 2024)
Abstract Several recent advances provide multiple health benefits to individuals with type 2 diabetes mellitus (T2DM). Pharmacological therapy is governed by person‐centered factors, including comorbidities and treatment goals. Adults with T2DM who have an established/high risk of atherosclerotic cardiovascular disease, heart failure, and/or chronic kidney disease, require a treatment regimen that includes agents that are proven to reduce cardiorenal risk. Weight management plays a key role in reducing glucose for patients with T2DM. A glucose‐reduction treatment regimen must consider weight management. Sodium glucose co‐transporter 2 (SGLT2) inhibitors reduce the risk of heart failure, cardiovascular and renal events. Glucagon‐like peptide‐1 (GLP‐1) receptor agonists allow better control of glycemia, promote weight loss and reduce the risk of cardiovascular events. Newer Glucose‐dependent insulinotropic polypeptide (GIP) and GLP‐1 dual agonist, which activate GIP and GLP‐1 receptors improve glycemic control and promote greater weight loss than GLP‐1 receptor agonists. Several novel drugs are in the clinical development phase. This review pertains to recent advances in pharmacological management of type 2 diabetes.